INVESTIGATING REPRESENTATIONS, OPINIONS AND ATTITUDES STUDENTS ON THE NATURAL ENVIRONMENT - CARMEN MIHAELA OLTEANU (Studia Universitatis Babes-Bolyai, 2012)
ABSTRACT. This paper provides a theoretical, methodological and applicative, integrative nature, starting from a comprehensive summary of relevant studies on environmental social representations, opinions and attitudes toward the natural environment. In this research we started from the idea that environmental attitudes can be formed by environmental ecological education, which aims to achieve three major objectives are closely interrelated, that targets cognitive, affective and practical attitude and action. This is done gradually through the educational process and school and extracurricular activities with specific environmental content. The study refers to highlight the spectrum of representations, opinions and attitudes of students green. It had, as a first objective assessment of NEP Scale (New Environmental Paradigm Scale) fidelity by calculating coefficient Alpha (α) Cronbach and found Alpha Cronbach global index of NEP Scale, the 15 items is acceptable, is over 0.75 and statistical analysis showed a satisfactory internal consistency of subscales / items of the NEP. The second objective of the study aimed at highlighting the relationship between the representations, opinions and attitudes about the natural environment and locus of control. The research hypothesis makes the prediction that the level of consciousness and ecological values, identified by social representations, pro-environmental views and attitudes of students is high. The assumption that, in an increased level of pro-environmental views and attitudes students have a sense of internal control more frequently than students was confirmed.